Regular charity giving behaviour among low-income households in Indonesia - Arsyianti, Laily Dwi; Kassim, Salina (IIUM Press, 2016)
How can a person in financial difficulty solve his problems? Islam gives the paradoxical solution of giving charity: the more you give, the more you get. Low-income earners should be encouraged to give charity as a means to free themselves from financial difficulties. This paper investigates the charity giving behaviour of low-income groups using an empirical study of factors affecting their regular charity giving. A total of 101 low-income households with monthly incomes of around USD80 in Jakarta were interviewed using the administered questionnaire approach. The data were analysed using logistic regression. The results highlight specific factors that significantly influence regular charity giving behaviour among the low-income households in Indonesia. This study hopes to provide important inputs to the relevant authorities and society on how to educate low-income households to manage their financial resources.